Visual Impairment Screening in Cibeusi Elementary School Students - Permana, Dea Aprilianti; Memed, Feti Karfiati; Radhiyanti Santoso, Putri Teesa (Althea Medical Journal, 2017)
Background: The World Health Organization (WHO) shows that there are around 153 million people with visual impairment due to uncorrected refractive error, mostly in 8â10 years. Screening of visual function in earlier age is important, because it is treatable. Correction of refractive error by using eye-glasses is the easiest and the cheapest way. This study aimed to identify the frequency of visual impairment and eye-glasses-used in children aged eight to ten in Cibeusi Elementary School. Methods: A descriptive study was conducted. This study was held in August 2014. Data were obtained from Cibeusi Elementary School in Jatinangor;Â simple random sampling technique was used to select 8â10 years old students. The total number of respondent was 101 students. Screening for visual impairment was performed using E-Chart. Result: Eleven eyes (5.44%) from a total of 202 eyes had visual impairment. Six (5.94%) students had visual impairment, whereas only 1 (1%) student used eye-glasses for improving his visual function. Visual impairment was considerably high in boy-students aged 8 yearsÂ and was most prevalence in 3rd grade students.Conclusions: There are visual impairments which are not corrected with sunglasses.